Benign Solvation Effect on Electrochemical Intercalation of Triethylmethyl Ammonium into Graphite from Propylene Carbonate. Issue 16 (1st January 2018) - Li, Jiayu; Huang, Yuhao; Wang, Hongyu
Abstract : Tetraethyl ammonium/triethylmethyl ammonium tetrafluoroborates dissolved in propylene carbonate (PC) are the most common non-aqueous electrolyte solutions for supercapacitors using both carbonaceous electrodes. In this work, they are applied in the graphite/activated carbon asymmetric capacitors, in which the charge storage at graphite negative electrode is based on the intercalation of quaternary alkyl ammonium cations. The capacitor containing triethylmethyl ammonium (TEMA + ) shows a much higher capacity and superior cycle-ability than that containing tetraethyl ammonium (TEA + ). In situ X-ray diffraction and in situ dilatometry are combined to determine the larger recoverable expansion in graphite negative electrodes due to a reversible intercalation of TEMA + . Electrochemical quartz crystal microbalance verifies the dramatic structural changes stem from the considerable co-intercalation PC molecules together with TEMA + . A benign solvation effect is proposed for facilitating the transportation and storage of TEMA + inside graphite.